Can We Predict Those With Osteoarthritis Who Will Worsen Following a Chronic Disease Management Program?. Issue 9 (29th July 2016) - Eyles, Jillian P.; Mills, Kathryn; Lucas, Barbara R.; Williams, Matthew J.; Makovey, Joanna; Teoh, Laurence; Hunter, David J.
Abstract : Objective: To identify predictors of worsening symptoms and overall health of the treated hip or knee joint following 26 weeks of a nonsurgical chronic disease management program for hip and knee osteoarthritis (OA) and to examine the consistency of these predictors across 3 definitions of worsening. Methods: This prospective cohort study followed 539 participants of the program for 26 weeks. The 3 definitions of worsening included symptomatic worsening based on change in the Western Ontario and McMaster Universities Osteoarthritis Index Global score (WOMAC‐G) measuring pain, stiffness, and function; a transition scale that asked about overall health of the treated hip or knee joint; and a composite outcome including both. Multivariate logistic regression models were constructed for the 3 definitions of worsening. Results: Complete data were available for 386 participants: mean age was 66.3 years, 69% were female, 85% reported knee joint pain as primary symptom (signal joint), 46% were waitlisted for total joint arthroplasty (TJA). TJA waitlist status, signal joint, 6‐Minute Walk Test (6MWT), depressive symptoms, pain, and age were independently associated with at least 1 definition of worsening. TJA waitlist status and 6MWT remained in the multivariate models for the transition and composite definitions of worsening. Conclusion: Participants reporting worsening on the transition scale did not consistently meet the WOMAC‐G definition of worsening symptoms. TJA waitlist status was predictive of the composite definition of worsening, a trend apparent for the transition definition. However, variables that predict worsening remain largely unknown. Further research is required to direct comprehensive and targeted management of patients with hip and knee OA.